Filling Data Gaps by Read‐across: A Mini Review on its Application, Developments and Challenges. Issue 8 (12th April 2019) - Kovarich, Simona; Ceriani, Lidia; Fuart Gatnik, Mojca; Bassan, Arianna; Pavan, Manuela
Abstract: Read‐across is a non‐testing data gap filling technique which provides information for toxicological assessments by inferring from known toxicity data of compound(s) with a "similar" property or chemical profile. The increased usage of read‐across was driven by monetary, timing and ethical costs associated with in vivo testing, as well as promoted by regulatory frameworks to minimize new animal testing (e. g., EU‐REACH). Several guidance documents have been published by ECHA and OECD providing guidelines on how to perform, assess and document a read‐across study. In parallel, much effort was invested by the scientific community to provide good read‐across practices and structured frameworks to enhance validity of read‐across justifications. Nevertheless, read‐across is an evolving method with several open issues and opportunities. A brief review is here provided on key developments on the use of read‐across, regulatory and scientific expectations, practical hurdles and open challenges. Abstract :